Resource Management Domains of Kharif and Rabi Season Fallows in Central Plateau Region of India: A Strategy for Accelerated Agricultural Development - Gupta, Raj; Kumar, Nirmal; Singh, SK; N. Sahoo, Rabi; Abrol, IP (Journal of Agronomy Research, 2019)
Over last few decades, acreage of total fallow lands (Kharif and Rabi seasons) in India has remained almost unchanged around 25Mha. The acreage of Kharif (summer) and Rabi (winter) Fallows in Madhya Pradesh (MP) are 1.98Mha and 5.51Mha, respectively. In the semi-arid agroclimatic zones of the states, Fallow-Wheat/Gram/Indian-Mustard cropping systems are practiced. After harvest of Kharif rice, kodo-kutki, maize or sorghum, farmers generally practice post-rainy season Rabi fallows in the sub-humid regions, south of Narmada River. Kharif fallowing is largely the result of the inability of the farmers to make planting dates independent of monsoon forecasts, and make efficient use of rain water. It appears that factors responsible for Kharif and Rabi fallows are distinctly different and a general consequence of distinctly different soil moisture regimes prevailing in the two crop seasons. Kharif and Rabi fallows have two distinct resource management domains. Whereas, Kharif fallows can be tackled with “PMP-dry seeding” agronomy, production constraints of Rabi fallows can be substantively tackled by shifting from tilled to zero-till agriculture with residue management to make efficient use of the conserved rain water. Some irrigation support will prove useful to tackle mid-season droughts in both situations. Conservation agricultural practices can significantly improve and stabilize crop yields in black soils and other associated soils of in the semi-arid tropics region of the Central India.
Keywords: Kharif / Rabi Fallow lands; Dry seeding; Seed priming; Black soils; RMD